Compression bending test for pvc pipe - Wan Ahmad, W.A.A (Universiti Malaysia Sarawak, UNIMAS, 2008)
In this project the superiority of the compression bending testing method will be demonstrated and compare with other conventional bending test method such as three point bending. Compression bending is a new bending test method. PVC pipe were used as the test specimen for these evaluation. PVC has excellent chemical resistance across its operating temperature range with a broad band of operating pressures due to its long term strength characteristics, high stiffness and cost effectiveness. The main focus in the compression bending test are measured the bending strength and bending modulus. Based on the result, the superiority of the compression bending test can be compared with the three point bending test. Instead of comparing this two bending test method, this project also compare the bending strength and the bending modulus of the PVC pipe that manufactured by two different countries.